أنماط التفكير الدماغي حسب نظرية نيد هيرمان وعلاقته بالمستوى الدراسي التحصيلي واختيار التخصص لدى طلبة التعليم ما بعد الأساسي في سلطنة عمان - مقحوصي، راشد سيف راشد (Kulliyyah of Education, International Islamic University Malaysia, 2022)
The study aimed to reveal the correlation existing between the patterns of brain thinking according to the Hermann model among post-basic education students in the eastern province of Job in the Sultanate of Oman. It also aimed to identify the prevailing cerebral thinking patterns according to Hermann's model, to reveal the influential and interactive role that exists between brain thinking patterns (ABCD) according to Herman's model on the one hand, to raise the level of achievement and sought to reveal the presence of statistically significant differences among post-basic education students in Al-Sharqiyah South Governorate according to Hermann's model which is attributed to the two variables (gender-specialization). In order to answer the research questions, the researcher used the descriptive and analytical method to identify patterns of brain thinking according to Ned Herman among post-basic education students, where the number of the study population reached 6995 students. A random sample of 654 male and female students was selected for the academic year of 2020-2021. The study used the Hermann Cerebral Control Scale as an instrument tool to collect the information. The study also used the simple statistical method such as mean scores, standard deviation, and percentages as well as inferential such as the double correlation of the Pearson correlation coefficient correlation coefficient, multiple linear regression and T-test. The study concluded that there is a statistically significant correlation between cerebral thinking patterns and the students with the proportion of 11.16% from the actual sample have a secondary preference for patterns. As for the basic patterns, the degree of students' possession of the patterns varied between having only one pattern, and some are having all the four patterns (ABCD). The results indicate that the prevailing pattern among students, their possession of all four types (ABCD), which constitutes (39.3%), and the results also showed that the patterns of brain thinking have an important and influential role in raising the level of academic achievement. The results of the cerebral thinking patterns (A), (B) and (C) and the left side pattern (A-B) showed that there are statistically significant differences at the level of (0.05) due to the gender variable, in favor of the female group. There were no statistically significant differences at the level (0.05) due to the specialization variable.